The Needs Analysis of Emodule for Learning Evaluation Courses According to the Independent Curriculum Integrating Islamic Values - Chandra, Artha Nesa; Fajar, Najmiatul; Idrus, Hadiyati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Things that lecturers must prepare for evaluating learning in lectures are RPS, teaching materials and assessment instruments. Lectures really need teaching materials that can support the lecture process. In accordance with current technological developments, electronic modules are needed that are in accordance with the independent curriculum. In addition, to instill religious values in students, the modules developed need to be integrated with Islamic science values. The aim of this research is to analyze the need for learning evaluation course emodules according to the independent curriculum integrating Islamic values of science. This research was conducted by conducting a literature study, interviews with lecturers in charge of the Learning Evaluation course, and distributing questionnaires regarding the need for teaching materials for the Learning Evaluation course. As a result, lecturers have made RPS and used media in learning, but have not included the independent curriculum as the newest curriculum. Apart from that, media that is more interesting for students is in the form of e-modules which contain material equipped with videos and attractive displays. In accordance with the West Sumatra government's policy regarding guidelines for religious values, because the majority of the population is Muslim, it is certainly necessary to include Islamic values in the electronic module. Therefore, it is necessary to develop a Learning Evaluation course emodule according to the independent curriculum that integrates Islamic values.